TRANSFORMING ENGLISH LANGUAGE EDUCATION: INNOVATIVE APPROACHES AND BEST PRACTICES - Heni Subagiharti; Diah Syafitri Handayani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Learning English is a mandatory subject and must be followed from elementary school to university level in accordance with the ongoing training plan in Indonesia. Students have difficulty mastering a new language, especially English, and teachers who are not native English speakers make it difficult for students to master it. As a result, some of the examples presented may be due to human error. It is accepted that changing English language learning through learning media will reduce weaknesses, difficulties in understanding learning and reduce human errors. This procedure includes media as an instrument to develop learning, one of which is through games, slides and interesting pictures. According to the instructions at each level of learning, this technique further develops learning for students. Apart from that, students are also enthusiastic about learning, can make coordinated efforts more easily between students, the environment and reality and are enthusiastic about progressing independently according to their respective abilities and interests.